1971
DOI: 10.1021/ja00739a043
|View full text |Cite
|
Sign up to set email alerts
|

.alpha.-Deuterium effects on the rates of solvolysis of a 2-adamantyl sulfonate ester

Abstract: Deuterium Effects on the Rates of Solvolysis of a 2-Adamantyl Sulfonate Ester1 Sir:In earlier reported work the -deuterium isotope effect has been developed as a criterion of solvolysis mechanism.2-17 It has been determined that for Sn2(1) This research was supported in part by Grant No. AT(11-1)-1008 from the United States Atomic Energy Commission (Document No. COO-1008-15). Electronic computations of rate constants were performed with the facilities of the Indiana Research Computing Center. NDEA Title IV Fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 1 publication
(1 reference statement)
1
19
0
Order By: Relevance
“…Reaction schemes of varying separately, the overall isotope effect becomes a complexity have been proposed (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction schemes of varying separately, the overall isotope effect becomes a complexity have been proposed (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…a mixture of two competing reaction paths. The By use of well known computational methods first path leads via the traditional (1) SN2 (12)(13)(14)(15)(16)(17)(18)(19) a suitable model of reasonable geometry transition state to products while the second may and bonding (force field) should then reproduce involve several carbonium ion-like species (2,5). the observed isotope effects (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In other words there is a significant nucleophilic participation by solvent in the solvolysis of these compounds in ethanolwater, although somewhat less in the case of 2,4,6-trimethylbenzyl chloride. The a-deuterium isotope effect for 2,4,6-trimethylbenzyl chloride in 80% trifluoroethanol-water (k,/kD = 1.16) actually exceeded the "upper limit" established by Shiner and Fisher for solvolysis of bengyl chlorides (13). The isotope effects for 2,4,6-tri-t-butylbenzyl chloride (Table 7) are also of considerable interest.…”
Section: Resultsmentioning
confidence: 86%
“…The 2,4,6-tri-t-butylbenzyl system are of interest, especially in view of some recent provides an interesting model for further work publications on the magnitude of a-deuterium in this field. In particular it is an interesting isotope effects (13,14). Our results are not of substrate for studying the magnitude of the --~-deuterium i s o t o~e effect for different leavine.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted maximal values for α-SDKIEs at 25°C for solvolysis of secondary alkyl tosylates and bromides are approximately 1.225 and 1.125, respectively (20,21). Indeed, two separate research groups reported α-SDKIEs for solvolyses of two different 2-adamantyl sulfonates at 25°C that are indistinguishable from the predicted maximal value (22,23). In contrast, the documented α-SDKIE values for the aqueous ethanolysis of 1-OTs fall in the range of 1.14-1.17 at 25°C (10).…”
Section: Secondary Deuterium Kinetic Isotope Effectsmentioning
confidence: 90%